Compulsive Exercise and Changes in Physical Activity Among Females: A Longitudinal Analysis During the First 12 Months of the COVID‐19 Pandemic - Hannah J. White; Chris J. McLeod; Emma Haycraft; Carolyn R. Plateau; Clare E. Holley; Gemma L. Witcomb (Brain and Behavior)
ABSTRACT This study had two aims; first to explore changes in compulsive exercise among adult females across the first year of the COVID‐19 pandemic, and second, to explore how changes to physical activity early in the pandemic impacted compulsive exercise. Participants were 174 adult females who completed online surveys four times (T1–T4) during the first 12 months of the pandemic. Participants reported changes in physical activity (T1) and completed the compulsive exercise test (CET) at each time point (T1–T4). Mixed ANOVAs with time (T1–T4) and group (did versus did not report changes in physical activity) as factors revealed that compulsive exercise significantly differed across timepoints for the whole sample. Furthermore, females who reported that their physical activity levels had changed early in the pandemic reported higher levels of CET Weight Control Exercise compared to those who reported no change. No significant interactions were found. Among this sample of adult females, attitudes towards exercise changed during the first year of the pandemic, which may reflect the impact of varying lockdown restrictions. Additionally, changes to physical activity early in the pandemic were linked with exercising to control body weight. This suggests that externally influenced changes in physical activity may be an influential factor in the development of compulsive exercise. This may have implications for understanding and managing risk in a range of transition situations that impact upon physical activity.